Sonographic Association and Prediction of Treatment Response to Medical Therapy in Patients with Benign Prostatic Hyperplasia: A Prospective Cohort Study - Mohit Mittal; Raghav Talwar; Ananya Dutta; Abhishek Kumar Shukla (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Benign Prostatic Hyperplasia (BPH) is mainly managed with alpha-blocker and 5 alpha reductase inhibitors. Non responders are offered surgery. To wait for the drug response is sometimes cumbersome for the patients with bothersome symptoms and may also lead to complications. On the other hand, some have minimal symptoms on drugs but silently develop obstructive complications. Aim: To understand the role of sonographic parameters of prostate and bladder of BPH patients in predicting and assessing response to medical treatment. Materials and Methods: This prospective cohort study was conducted in the Department of Urology at Army Hospital Research and Referral, New Delhi, India. The duration of the study was 15 months, from October 2017 to January 2019. A total of 100 consecutive patients of BPH with Prostate-specific Antigen (PSA) <4 ng/mL and prostate of >35 cc were given three months of alpha-blocker and dutasteride. Based on there subjective response, they were grouped into Symptomatic Improved (SI) and Not Improved (NI) group. Values of sonographic parameters including Prostate Volume (PV), prostatic capsular artery Resistance Index (RI), Intravesical Protrusion of Prostate (IPP), Detrusor Wall Thickness (DWT) and Post-void Residual volume (PVR), as well as, International Prostate Symptom Score (IPSS) and Uroflowmetry (UFM) at baseline and after three months of treatment were analysed and compared in both the groups. The significance of change in parameters was analysed using paired t-test and two sample Student’s t-test. Results: The mean age of the study participants was 64.8±5.86 years. There was an association between IPSS and flow with initial reading of PV, PVR, DWT, RI and IPP. Post-treatment both, SI (n=74) and NI (n=26) group showed valuable difference in DWT, PV and PVR but it was significantly more in improved group. Significant change in RI was observed only in SI group and IPP did not change in either group. Area Under Curve (AUC) under Receiver Operating Characteristic (ROC) was suggestive of higher sensitivity for IPP in predicting drug outcome. Conclusion: Combined use of Ultrasonography (USG) and Kidney, Ureter, and Bladder (KUB) parameters as described above like RI, DWT, PV and IPP can be used to predict and assess the objective response to drug in BPH. This helps in determining therapeutic plan and the need for further medical therapy or surgical intervention.